The role of mothers in meeting nutritional needs of children with grade II dengue hemorrhagic fever - Hermansyah Hermansyah; Elmiadi Elmiadi; Nurleli Nurleli; Nurhayati Nurhayati; Helly Susanti (AcTion: Aceh Nutrition Journal, 2024)
Grade II Dengue Hemorrhagic Fever (DHF) in children often leads to symptoms, such as nausea, vomiting, appetite loss, extended hospital stay, and delayed recovery. Proper nutrition is essential for managing these symptoms and supporting recovery. Mothers play a critical role in fulfilling their children’s nutritional needs. This study explored the role of mothers in meeting the nutritional needs of children with Grade II DHF in the Pediatric Ward at Meuraxa Hospital Banda Aceh municipality. Using a qualitative case study approach, data were collected from three mothers whose children were treated for two weeks, from admission to discharge, during the study period in August 2021. Data were gathered through interviews, observations, and medical records and then analyzed through thematic content analysis focusing on education, caregiving, and nurturing. The results showed that, while mothers followed hospital feeding schedules, they faced difficulties in encouraging their children to eat because of their low appetite. They fostered a supportive environment using storytelling and praise but avoided discussing meal nutrition, assuming that their children were too young to understand. In conclusion, mothers demonstrated strong caregiving. Challenges include limited nutritional knowledge and difficulty in making the food appealing. Enhancing maternal knowledge and feeding strategies can support faster recovery of children with DHF.